Frequency dependence of quality factor in vibration energy harvesting - Ashraf, K. (2013)
With the fast development in the ubiquitous computing and wireless sensing technologies, a new era of smart cities is evolving. Future smart cities will gather sensory data, needed for effective management of the city, using wireless sensor networks. Exhaustive power sources such as batteries need periodic replacement and hence increase the cost of ownership of wireless sensor network. On the other hand, renewable vibration energy is found in abundance in many target environments of wireless sensor network, which can be harvested to power up the sensor node. The average power of a vibration energy harvester strongly depends on the frequency of vibration and quality factor of the harvester. Unfortunately, most of the environmental vibrations occur in a low frequency range of few tens of Hz. This paper analytically investigates the challenges in designing a low frequency energy harvester with a high quality factor. Â© 2013 IEEE.